Study on ability of palm oil as viscosity index improvement (VII) additive in thermal stability (base mineral oil - Cooking palm oil) - Hasnul, Hadi; Liyana, Tajul; M. S., Hussin; Zailani, Zainal Abidin; Mohd Fidzwan, Md Amin Hamzas; Muhammad Syahril, Bahari (Praise Worthy Prize S.r.l., 2013)
Link to publisher's homepage at http://www.praiseworthyprize.com/